(untitled) (Nigerian Journal of Technology, 2017)
This paper presents the design of a cost effective energy system for National Centre for Hydropower Research and Development (NACHRED) building to supply its daily energy requirements. The daily hourly load demand of the building was measured with FLUKE 434 Series II Energy Analyzer. The measurement was grouped into two namely: category 1 and category 2. In category 1, the essential electrical load demand excluding air conditioner system was measured for 3 consecutive days while in category 2 the total daily load demand including air conditioner system was also measured for three consecutive days. HOMER pro3.2 was used to size and simulate photovoltaic system required for the two categories. The system in category 1 with the load of an average consumption of 36.34kWh/d, is considered as a cost effective system for the building, as compared to one in category 2 with the load of an average consumption of 198.1kWh/d. http://dx.doi.org/10.4314/njt.v36i4.30